Norethindrone substituted for megestrol in the treatment of metastatic endometrial carcinoma: Three cases - William L. Read; Sumita Trivedi; Felicia Williams (Elsevier, 2017)
Megestrol is an effective palliative treatment for endometrial carcinoma. Some persons with progestin-responsive cancer continue on hormonal therapy for months or even years. In persons who respond to megestrol, long term use can cause weight gain and other side effects via activity of the drug at the corticosteroid receptor. Norethindrone is a progestin which has been used clinically for decades and which is without corticosteroid activity. We report three women with metastatic endometrial cancer responding to megestrol for whom a switch to norethindrone decreased weight gain with continued cancer control. A clinical trial of first line norethindrone for metastatic endometrial cancer could benefit people with this disease.